Validación preliminar de la prueba diagnóstica "Anigen rapid b brucella ab test" para la detección de anticuerpos contra brucella abortus en suero bovino y comparación con las pruebas SAT y RB - Vela Chiriboga, Andrea Carolina (2013)
Brucellosis is an infectious disease of mammals caused by bacteria of the genus Brucella that has humans as accidental hosts, therefore is considered by the World Organization for Animal Health (OIE) as one of the most important zoonoses, due to its global distribution, the great impact in public health and in social, and economical aspects . The diagnostic is based on clinical history and consistent clinical signs, but as the latter are not pathognomonic, the isolation of the causal agent is needed to make a definitive diagnosis. The World Health Organization (WHO) classifies this genus in Risk Group III, as the management of the infected material requires strict biosafety measures, so it is necessary to resort to other diagnostic techniques in serum; however, many of the available available tools need to be carried out in a laboratory, require trained personnel or the results are not obtained immediately. For all these reasons there is a growing need for a rapid field test.